Comparison of Stream Characteristics of Forested Subwatershed and Deforested Watershed in Mangunan Area, DIY - Sudarmadji, S (Forum Geografi, 1992)
Land use changes from forestedÂ  into unforest catchment result negative effects to the environment, including to the hydrological and soil condition of the area. To improve the hydrological and soil conditions serious attemps are required, and they take a long period to realize. The Mangunan Girirejo area (which is located in the Bantul regency, Yogyakarta Special Province) is one of pilot projects managed by the Gadjah Mada University. Among itâs activities the project tried to improve critical land by reforesting the area withÂ  some kinds of plant. From the hydrological points of view this attemps should be evaluated, by comparing runoff from two adjacent catchments having similar conditions expect those on the land use. One of them is forested catchment, while the other is unforest catchment. The studyÂ  was conducted in the Mangunan Girirejo area using two small subcatchments. The forested subccatchment used for the study having an area 2.225 hectares. The forested subcatchment in now mostly covered by the pinus mercusii, acacia auliculiformis and malaleuca leucacendra, while the unforested subcatchment is used for the dry field ultivation, and dominantly casava, beam, and corn were planted in the subcatchment. About three month was needed for observing hydrological parameters (from January to March 1993). During the research some hydrological component such as rainfall, overlandflow, seepages, and runoff were observed. Rainfall in the study area generallyÂ  having less than 100 mm depth, falling in shorter than 4 hours duration. As an input in the hydrological system of the subcatchment, the rainfall did not always result runoff. In the forested subcatchment rainfall did not always result runoff. In the forested subcatchment rainfall higher than 10 mm depth result runoff, while in the unforested subcatchment the 5 mm rainfall is concidered as minimum rainfall to result runoff. The runoff hydrolographs of the two subcatchment having different characteristics. Although they have quick rise, the time of rise in the unforested subcatchment is shorter that those to the forested subcatchment. The hydrographs of the forested subcatchment have lower peaks than the unforested subcatchment, however the time base of hydrographs in the unforested subcatchment are longer. Chemical substances those which dominated the rock forming minerals (Ca, Mg, Na, K, HCO3, SO4, and SiO2) significantly increased from rainfall to runoff. The highest concentration found in the surface runoffand seepages. However if the one compared the concentration of the chemicals in the water originated from forestsed and underforested watershed he may say that the concentration of the chemical in water from unforested subcatchment is generaly higher than those from the forested subcatchment is generaly higher than those from the forested subcatchment. Runoff draining from unforested subcatchment having a higher SO4 and PO4 concentration sompared to those originated from forested subcatchment. The high concentration of the substances may bee caused by use of fertilizer by farmers in the unforested subcatchment.